Cold atom reflection from curved magnetic mirrors - Hughes,IG; Barton,PA; Boshier,MG; Hinds,EA (1997)
Multiple bounces of cold rubidium atoms have been observed for times up to one second in a trap formed by gravity and a 2 cm-diameter spherical mirror made from a sinusoidally magnetized floppy disk. We have studied the dynamics of the atoms bouncing in this trap from several different heights up to 40.5 mm and we conclude that the atoms are reflected specularly and with reflectivity 1.01(3). Slight roughness of the mirror is caused by harmonics in the magnetization of the surface and by discontinuities at the boundaries between recorded tracks. As the next step in this atom optics program we propose using a magnetic mirror to create a 2D atomic gas. We discuss how cold atoms can be loaded into the ground state of a static magnetic potential well that exists above the surface of the mirror as a consequence of the intermediate-field Zeeman effect. ©2004 Copyright SPIE - The International Society for Optical Engineering.